Socio-demographic profiles of the delayed diagnosed patients in RNTCP, Anand District. - Donald Christian; Uday Shankar Singh; Sidhyartha Mukherjee; Deepak Sharma (Healthline, 2010)
It would be worth to consider socio-demographic characteristics of the patients on DOTS (Directly Observed Treatment Short course), as the therapy requires a long term adherence. Material & Methods: Design: Cross-sectional study, Participants: 100 diagnosed TB patients on DOTS, from all TB units (25 from each TU) of Anand District, who had reported 3 weeks or later to health care center, after the onset of symptoms of TB. Information was filled up in a pretested questionnaire and the data was analyzed. Results: Among 100 TB patients (68 males and 32 females), 75% of the subjects had an education below 9th standard. 46% of subjects were laborer. 65% were self-dependent. Most of the respondents (75%) preferred government facility. Conclusion: The socio-demographic characteristics of DOTS patients are found to be of such levels that could have a pivotal role in the treatment success. They also need to be addressed under the program in such a manner that those characteristics don’t prove to be a barrier to treatment success.